2020
DOI: 10.1111/all.14250
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting microbiotas between Finnish and Estonian infants: Exposure to Acinetobacter may contribute to the allergy gap

Abstract: Background Allergic diseases are more common in Finland than in Estonia, which—according to the biodiversity hypothesis—could relate to differences in early microbial exposures. Methods We aimed at defining possible microbial perturbations preceding early atopic sensitization. Stool, nasal and skin samples of 6‐month‐old DIABIMMUNE study participants with HLA susceptibility to type 1 diabetes were collected. We compared microbiotas of sensitized (determined by specific IgE results at 18 months of age) and unse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…Bacteria characterize best the differences in microbial communities and are not equal in their immunomodulating potential. For example, Acinetobacter species, both on human skin and on mice, are effective immunoregulators and associated with allergy and asthma risk 10‐12 . Maternal carriage of Prevotella copri during pregnancy decreases the offspring's risk of allergic disease and asthma 13 .…”
Section: Biodiversity Fundamental For Human Lifementioning
confidence: 99%
See 1 more Smart Citation
“…Bacteria characterize best the differences in microbial communities and are not equal in their immunomodulating potential. For example, Acinetobacter species, both on human skin and on mice, are effective immunoregulators and associated with allergy and asthma risk 10‐12 . Maternal carriage of Prevotella copri during pregnancy decreases the offspring's risk of allergic disease and asthma 13 .…”
Section: Biodiversity Fundamental For Human Lifementioning
confidence: 99%
“…For example, Acinetobacter species, both on human skin and on mice, are effective immunoregulators and associated with allergy and asthma risk. [10][11][12] Maternal carriage of Prevotella copri during pregnancy decreases the offspring's risk of allergic disease and asthma. 13 In the gut, Morganella species has a potential causal effect on major depressive disorder.…”
mentioning
confidence: 99%
“…Similar findings have come from Finland, which has become a hot bed of comparative studies between sub-populations in close proximity with contrasting microbial exposures. A recent study provided evidence that relative exposures to one particular bacterium common in the rural environment, Acinetobacter, correlates with a striking difference in allergy risk between infants in Finland and nearby Estonia (Ruokolainen et al, 2020). This study reported significant differences in microbial diversity and community composition with the genus Acinetobacter more abundant among Estonians whose children have a lower risk of allergy than Finnish children.…”
Section: Evidence From Epidemiological Studiesmentioning
confidence: 77%
“…Similar findings have come from Finland, which has become a hot bed of comparative studies between sub‐populations in close proximity with contrasting microbial exposures. A recent study provided evidence that relative exposures to one particular bacterium common in the rural environment, Acinetobacter , correlates with a striking difference in allergy risk between infants in Finland and nearby Estonia (Ruokolainen et al , ).…”
Section: Evidence From Epidemiological Studiesmentioning
confidence: 99%
“…(Table 1) [28][29][30][31][32][33][34][35][36][37][38][39] Illustrates examples of key microbes in different body location that carry out significant function for the whole human.…”
mentioning
confidence: 99%